Pemetaan satuan geomorfologi daerah kota Agung propinsi Lampung berdasarkan interpretasi citra synthetic aperture radar (sar) - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Pertanian UGM, 1998)
ABSTRACT Kotaagung area Lampung Province was selected as investigation area to study the use of SAR image in geomorphologic mapping. Based on the results of the visual SAR image interpretation it was found that in the investigation area there were 3 geomorphologic units and 28 geomorphologic sub units in which the forming of the landforms were influenced by tectonic, volcanic, and fluvial processes. SAR image analysis was useful in identifying and delineating geomorphologic units and sub units in the investigation area. SAR image particularly helpful for regional geomorphologic mapping in area of high relief , dense vegetation , cloudy and which are difficult to be visited directly.